A new species of Bulbophyllum (Orchidaceae: Epidendroideae) from Kalimantan Barat, Indonesia - Kurniawan, Firman H.; Yudistira, Yuda R.; Mustaqim, Wendy A. (Phytotaxa, 2022)
Bulbophyllum sungaiutikense is a new orchid species from Kapuas Hulu, Kalimantan Barat, Indonesia, and a member of the B. sect. Beccariana, allied to B. nabawanense. It differs from the latter in having tetragonal lateral sepals with an elongate triangular apical part, long acuminate petals, different and longer labellum with flattened base and verrucose adaxial surface. Notes on ecology and phenology, discussion of morphologically similar species, amendments to the key to B. sect. Beccariana in Borneo, illustrations and photographs are included here.